Software as a support tool in the artistic gymnastics women in Venezuela - Ramirez, E. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction In the specialty of the use of sports technology and technology support for sports and the training of specialists in this area is limited in the Spanish language. This has led to the present investigation which may lead to implementation of professional development programs in which new technologies in the specific context of the womens artistic gymnastics (GAF) may be implemented. This also enables both coaches and trainers as young monitors and facilitators who are initiated in this discipline, to have an element of support or help tailor to their needs. This would include utilities related to the definition of techniques to correct implementation of the different elements of gymnastics and its teaching methodologies while providing further support to assist in the planning and control of the process of training. Such support will enable better monitoring of the training process and greater consistency of approach in teaching gymnastics exercises. It will also result in an increase in the level of technical equipment and its future development. Methods The study sample was composed of all of the specialists in artistic gymnastics women (because the population is not too large) who work with girls or boys in the categories pre-infant, child AB, juvenile and adult throughout Venezuela. Thirty questionnaires were collected to cover the diagnostic phase and in the validation of the software in the study. 15 interviews were conducted in Phase 1 (diagnosis) and 10 in phase 2 (validation). In addition, 2 discussion groups, with the participation of specialists from 5 and 4 artistic gymnastics groups respectively in the diagnostic phase, and two focus groups in the validation phase with the participation of specialists from 6 artistic female gymnastics provided additional information. Results The general training in terms of technical support for the evaluation of artistic gymnastics techniques in Venezuela is very low. There appears to be some difficulty in the understanding of the principles of scientific training such as mechanical and physiological phenomena which, hinders the coaches. Skills are very basic and this in turn ensures the information, content and methodology of teaching and learning software and website must be tailored at a basic level. . Preferences towards practical examples as proposed using relevant software tools and the website and required to visualize practical situations is necessary for diagnostics in performance. Discussion Evaluation software and website have revealed that they are appropriate and effective tools for the design of training sessions. Both professional coaches and trainers need to individualize the teaching and learning process (monitoring and control) of the gymnasts, which can adapt to their work routines with ease. References